Holocene colluvial chronology in a sub‐arctic esker landscape at Kuttanen, Finnish Lapland: kettleholes as geo‐ecological archives of interactions amongst fire, vegetation, soil, climate and geomorphological instability. (3rd December 2014) - Matthews, John A.; Seppälä, Matti
Abstract : Excavations were made in the colluvial deposits of seven kettleholes in a sandy esker at Kuttanen, northwestern Finnish Lapland. The Holocene history of forest fires and the associated colluvial activity initiated on the slopes of the kettleholes were reconstructed based on 131 radiocarbon dates from charcoal layers. These dates were supplemented by luminescence dating of colluvial sand layers. The first forest fires occurred ∼9000 years ago following the immigration of Pinus sylvestris about 1000 years after deglaciation. Evidence of forest fires and colluvial activity increased with the density of the pine forest, reaching a maximum during the Holocene Thermal Maximum between ∼8000 and 4000 cal. a BP, declining thereafter to a minimum in the last ∼500 years. This multimillennial‐scale pattern corresponds with forest fires being triggered by lightning strikes during the warmest summer weather of the Holocene, which also produced heavy rain and slope wash from convective storms. The 50 forest fires identified over the Holocene indicate a long cycle in fire frequency of 1 in ∼200 years, which appears to reflect the average successional recovery time of the forest. Complex interactions amongst vegetation, fire and climate may account for little or no association between 23 centennial‐ to millennial‐scale clusters of forest fires/colluvial events and Holocene temperature or precipitation anomalies. Buried podzols indicate five phases of soil formation and hence low levels of landscape disturbance. The kettleholes and their colluvial deposits therefore provide a unique geo‐ecological archive that has led to new insights into the geo‐ecological interactions that affect environmental change in the sub‐arctic landscape.